2013 International Conference on Advanced Logistics and Transport 2013
DOI: 10.1109/icadlt.2013.6568434
|View full text |Cite
|
Sign up to set email alerts
|

Energy-efficient street lighting through embedded adaptive intelligence

Abstract: Abstract-Streetlights place a heavy demand on electricity usage, providing significant financial and environmental burdens. Consequently, initiatives to reduce energy consumption have been proposed, usually by turning off or dimming the streetlight. In this paper, we propose an adaptive lighting scheme based on traffic sensing, which adaptively adjusts streetlight brightness based on current traffic conditions. The algorithm has been validated through simulation using the SUMO and OMNeT++ tools and, for two di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 10 publications
0
25
0
6
Order By: Relevance
“…Before detailing the proposed TALiSMaN-Green street light control scheme, we first give a brief overview of the functionality of TALiSMaN [19]. The aim of this scheme is to set lighting conditions optimally to satisfy different road users' needs.…”
Section: Talismanmentioning
confidence: 99%
See 1 more Smart Citation
“…Before detailing the proposed TALiSMaN-Green street light control scheme, we first give a brief overview of the functionality of TALiSMaN [19]. The aim of this scheme is to set lighting conditions optimally to satisfy different road users' needs.…”
Section: Talismanmentioning
confidence: 99%
“…In our previous work [19], we demonstrated that an adaptive street lighting scheme, known as Traffic-Aware Street Lighting Scheme Management Network (TALiSMaN), can substantially improve the energy efficiency of state-of-the-art lighting schemes while maintaining their usefulness to road users. That scheme used sensor nodes mounted on street lights to detect passing pedestrians and motorists.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in next stage of our studies we are going to develop a predictive control algorithm, with ability to adapt to the changes of the seasons, months and schedules and even able to react to unexpected changes in the environmental parameters, etc. (Oezluek et al 2010;Alzubaidi and Soori 2012;Lau et al 2013;Novak et al 2013). Another important question is the Internet protocol IPv6 and an Internet of Things (IoT) technologies growing.…”
Section: Future Workmentioning
confidence: 99%
“…This includes our early work in this field [27], where we proposed an algorithm which adjusted streetlight brightness in response to nearby road users, reducing the energy consumption by 30% compared to state-of-the-art schemes. Importantly, many of these existing works (including our own) were primarily aimed at reducing energy consumption, with very little consideration given to the associated impact of such schemes on the usefulness of the streetlights.…”
Section: Introductionmentioning
confidence: 99%
“… We propose a new adaptive street lighting algorithm (based on that we proposed in [27]), TALiSMaN, which tailors its operation to different road users. This is based on the utility model we presented in [28], and we present a more complete description of this here.…”
Section: Introductionmentioning
confidence: 99%